2005
DOI: 10.1002/jms.931
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Boc‐ α,β‐ and β,α‐peptides and a pair of diastereomeric β,α‐dipeptides by positive and negative ion electrospray tandem mass spectrometry (ESI‐MS/MS)

Abstract: Positive and negative ion electrospray ionization (ESI) tandem mass spectral study of a new series of hybrid peptides, viz, BocN-alpha,beta-peptides and BocN-beta,alpha-peptides, synthesized from C-linked carbo-beta3-amino acids [Caa (S)] and L-Ala has been carried out. The alpha,beta-peptides have been differentiated from beta,alpha-peptides by the collision-induced dissociation (CID) of [M + H]+ and [M - H]- ions in positive and negative ion ESI-MS respectively. The fragment ion [M + H - C(CH3)3 + H]+ formed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 22 publications
(44 citation statements)
references
References 26 publications
2
42
0
Order By: Relevance
“…34 -38 We have reported earlier ESI MS/MS of a series of Boc-protected carbopeptides, 34 and differentiated both positional and diastereomers. 35,36 We have also shown that MS/MS of some of the˛, -/ ,˛-37 peptides can be used to identify the -NH hydrogens that participate in the 'H' bonding leading to helical structures in solution phase. Recently, Talaty et al reported an interesting mass spectral study on the influence of the presence and position of an alternative amino acid including two nonnatural amino acids viz.ˇ-alanine (X), -aminobutyric acid (X) on the formation of b n C and y n C ions from a series of protonated tetrapeptides with general sequence XAAG, AXAG, and AAXG.…”
Section: E=1; R=hmentioning
confidence: 95%
“…34 -38 We have reported earlier ESI MS/MS of a series of Boc-protected carbopeptides, 34 and differentiated both positional and diastereomers. 35,36 We have also shown that MS/MS of some of the˛, -/ ,˛-37 peptides can be used to identify the -NH hydrogens that participate in the 'H' bonding leading to helical structures in solution phase. Recently, Talaty et al reported an interesting mass spectral study on the influence of the presence and position of an alternative amino acid including two nonnatural amino acids viz.ˇ-alanine (X), -aminobutyric acid (X) on the formation of b n C and y n C ions from a series of protonated tetrapeptides with general sequence XAAG, AXAG, and AAXG.…”
Section: E=1; R=hmentioning
confidence: 95%
“…The negative ion ESI of di-(11-16) tetra-(17-18) and hexa -ions [39,41,[43][44][45][46]54]. The formation of these ions may presumably be due to a 1,3-H migration from -NH-to the ‛ O of the butyloxy group leading to the elimination of tert-butanol by charge-remote fragmentation [46].…”
Section: Negative Ion Cid Of Isomeric Peptide Acidsmentioning
confidence: 99%
“…The tandem mass spectrometry (MS/MS) of protonated [21][22][23][24][25][26][27], deprotonated peptides [28][29][30][31][32][33] in electrospray ionization (ESI) and matrix-assisted laser desorption/ionization (MALDI) [34][35][36][37] have been used for structure elucidation of peptides. There are very few reports in the literature on the mass spectral study of peptides derived from non-natural amino acids [38][39][40][41][42][43][44][45][46][47][48]. We have reported ESI-MS/MS of a series of Boc-protected carbopeptides [39][40][41][42][43][44][45][46][47][48], and differentiated both positional and diastereomeric isomers [39][40][41][42][43][44][45][46]48].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, despite the growing interest in the use of ␤-amino acids in constructing peptides that are protease resistant [8] or that have unique architectures [9], the gas-phase chemistry of protonated ␤-amino acids and their peptides have received much less attention. Key exceptions include studies that have shown that ␤-alanine has a higher proton affinity than ␣-alanine [10]; protonated ␣-and ␤-alanine (1 and 2; see Scheme 1) fragment via different pathways [11]; the relative abundances of sequence ions in ␣-and ␤-alanine containing peptides can be different [12]; and ␤-alanine peptides can be identified via CID of the Boc-protected derivatives [13]. Furthermore, Seebach's group has shown that tandem mass spectrometry of protonated ␤-peptides can be used to confirm their structures via the formation of sequence ions [14].…”
mentioning
confidence: 99%